Integrating CTI and threat modeling for cyber resilience: An AHP assessment - Luka Podlesnik; Igor Bernik; Anže Mihelič (PLoS ONE, 2025)
Cyber resilience has emerged as a critical objective for modern cybersecurity programs, emphasizing not only prevention but also the ability to anticipate, withstand, recover from, and adapt to cyber threats. Two disciplines, cyber threat intelligence (CTI) and threat modeling, are increasingly recognized as fundamental to achieving these goals. While each offers unique benefits, their integration and potential synergistic benefits remain underexplored in empirical research. This study employs the Analytic Hierarchy Process (AHP) to evaluate the comparative effectiveness of an integrated CTI-threat modeling approach versus its standalone implementations. Drawing on judgments from cybersecurity experts across government, finance, and telecommunications sectors, the evaluation is structured around four resilience criteria: anticipate, withstand, recover, and adapt. The results demonstrate a strong preference for integration, particularly in supporting anticipation and operational continuity. These findings provide empirical validation for theoretical arguments and highlight the need for standardized integration frameworks to operationalize this approach and enhance resilience in practice.